Historical ostriches in the Libyan Desert, with ecological and taxonomic considerations - Arnd Schreiber (Natural History Sciences)
Many historical records extend the known range of the African ostrich Struthio camelus to include almost the entire state territory of Libya. This significant expansion augments the spatial potentialities to reintroduce captive-bred progeny of the endangered red-necked ostriches (S. c. camelus) from zoos and wildlife centres. The latest Libyan ostriches lingered in Cyrenaica and Fezzan into the late 19th century, and presumably near Kufra into the 1930s. Their extermination coincided with the occupation by colonial European administrations. These east Saharan biotopes are extraordinarily resource-poor and climatically challenging due to wide thermal amplitudes and extreme drought. Old photographs from Kufra and Wadi Howar leave undecided if the Libyan ostriches adhered to the subspecies S. c. camelus, which appears possible, or if additional, partly substantiated but yet unconfirmed claims should be heeded which demand up to three subspecies in North Africa. A review of taxonomic interpretations reveals a weak foundation by reliable data of a pan-Saharan subspecies S. c. camelus, and additional research is suggested to provide a sound taxonomic concept, not least for the management of various regional breeding lineages in zoos, which safeguard the survival of this endangered bird. As an auxiliary finding, African wild dogs (Lycaon pictus) are attested as inhabitants of the southern Libyan Desert until the 1930s, where they had preyed upon the now equally extinct ostriches.